Blockchain’s Impact on Morocco’s Financial Sector: Opportunities and Challenges - Asly Ishaq; Essabbar Driss (ITM Web of Conferences)
The adoption of emerging technologies in the finance industry, such as blockchain, promises to provide new perspectives on data security and business processes. This advanced innovation paves the way for unprecedented financial and organizational optimization, transforming not only processes and structures, but also fundamental paradigms of trust and knowledge. The financial industry faces numerous challenges in combating fraud and embezzlement, due to the complexity and scale of its operations. Therefore, the infrastructure provided by the blockchain system helps reduce costs related to intermediaries, enhances security, and improves trust between stakeholders, thanks to the principle of decentralization and the immutability of its ledger. Furthermore, this technological revolution offers financial actors the ability to create new services and solutions in order to meet the needs of several business activities, especially those with complex supply chains. A perfect use of it, will certainly develop the standards of this industry and stimulate innovative economic growth. Although the blockchain offers substantial opportunities for the financial sector, its potential can only be fully achieved with adequate regulatory support, as a way to steer the system toward a more digital and inclusive economy. After a presentation of blockchain technology and its mode of operation, we will be focusing on its potential in finance and how it might provide creative accounting and financial management solutions.